Effects of High Levels of Dietary Linseed Oil on the Growth Performance, Antioxidant Capacity, Hepatic Lipid Metabolism, and Expression of Inflammatory Genes in Large Yellow Croaker (Larimichthys crocea) - Li, Xueshan; Chen, Qiuchi; Li, Qingfei; Li, Jiamin; Cui, Kun; Zhang, Yunqiang; Kong, Adong; Zhang, Yanjiao; Wan, Min; Mai, Kangsen; Ai, Qinghui (Frontiers in Physiology, 2021)
A growth experiment was conducted to evaluate the effects of dietary fish oil (FO) substituted with linseed oil (LO) on the growth performance, antioxidant capacity, hepatic lipid metabolism and expression of inflammatory genes in large yellow croaker. Fish (initial weight: 15.88 ± 0.14 g) were fed four experimental diets with 0% (the control), 33.3%, 66.7%, and 100% of FO substituted with LO. Each diet was randomly attributed to triplicate seawater floating cages with 60 fish each cage. Results showed that the growth performance of fish fed the diet with 100% LO was markedly decreased compared with the control group (P < 0.05), while no remarkable difference was observed in the growth of fish fed diets within 66.7% LO (P > 0.05). The percentage of 18:3n-3 was the highest in the liver and muscle of fish fed the diet with 100% LO among the four treatments. When dietary FO was entirely replaced by LO, fish had markedly higher contents of total cholesterol, total triglyceride, and low-density lipoprotein cholesterol, as well as activity of alanine transaminase in the serum than the control group (P < 0.05). The concentration of malondialdehyde was markedly higher, while the activity of catalase was markedly lower in fish fed the diet with 100% LO than the control group (P < 0.05). When dietary FO was entirely replaced by LO, fish had significantly higher hepatic lipid content, transcriptional levels of fatp1 and cd36, the expression of CD36 protein, as well as significantly lower the transcriptional level of cpt-1 and the expression of CPT-1 protein than the control group (P < 0.05). As for the gene expression of cytokines, fish fed the diet with 100% LO had markedly higher transcriptional levels of il-1, tnf and il-6 than the control group (P < 0.05). In conclusion, the substitution of 66.7% FO with LO had no significant effects on the growth performance of fish, while 100% LO decreased the growth performance and increased inflammation and hepatic lipid content of fish. The increase of hepatic lipid content was probably by increasing fatty acid uptake and decreasing fatty acid oxidation in fish.